2009
DOI: 10.1136/jech.2008.082909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexually transmitted disease syndromes in tribal population of central India

Abstract: The low level of STD syndromes among tribal populations offers an opportunity to prevent a potential epidemic in this disadvantaged community. As no baseline data are available, the findings form the basis for future work in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…It contrasts with the study performed by Rao VG. et al, where age group 30-34 was the maximum sufferers 20. This contrast is probably because the study included only married individuals and population included in our study may have less knowledge regarding STIs.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…It contrasts with the study performed by Rao VG. et al, where age group 30-34 was the maximum sufferers 20. This contrast is probably because the study included only married individuals and population included in our study may have less knowledge regarding STIs.…”
mentioning
confidence: 74%
“…Studies conducted in various parts of South East Asia have shown almost double prevalence of STIs among women. 16,17,20 In developing nations, women have limited access to information or health services than men and they are too busy in household or child caring activities. [21][22][23] They have symptoms for longer period and less often they seek treatment than men.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sexually transmitted diseases could be as high as 17.6% among females from tribal population [13] to varying degree in metropolitan cities in India [14]. The incidence of chlamydial infection in female sex workers in Surat was estimated to be 8.5% using PACE2 test (non-amplified DNA probe assays for C. trachomatis and N. gonorrhoeae ; Gen-probe San Diego, USA) while in Ahmedabad it was almost double [8].…”
Section: Introductionmentioning
confidence: 99%
“…The commonest syndrome among women was vaginal discharge 16% while in men was burning micturition 1.8%. 10 …”
Section: Discussionmentioning
confidence: 99%